Identifying Alterity and Altering Identity - Brahim, Abdelghani Nait (Mediterranean Journal of Social Sciences, 2011)
Negative attitudes towards foreign cultures among certain categories of people in majority Islamic countries are often the result of their representations of the Other, their conception of alterity, of their identity and the relation between them, their vision of the implications of the confrontation with/or coexistence of different cultures in the same physical space or through mediated spaces. These representations have become a culture in its own right, giving birth to a categorisation of people within the same society and of peoples of the world. This paper will attempt to reveal the way this culture dichotomy operates and will analyse the mode its ideological base defines the dichotomy of alterity/identity. It will also suggest directions of reflexion towards the possibilities of forging a counter-culture which can stand as a new form of liberating discourse.